Leaf Traits as Indicators of Resource-Use Strategy in Floras with Succulent Species - Vendramini, Fernanda; Díaz, Sandra; Gurvich, Diego E.; Wilson, Peter J.; Thompson, Ken; Hodgson, John G. (The New phytologist, 2002)
• Associations between specific leaf area (SLA), leaf water content (LWC) and leaf thickness (LT) in 77 species were analysed to identify which of these traits gave a better indicator value of general plant resource-use strategy within the flora of central-western Argentina, in which succulent species are common. • When all species were considered together, SLA and LWC were not significantly correlated. All high-SLA tender-leafed species showed high LWC. Low SLA, however, was associated both with low LWC (sclerophyllous species) and with high LWC (succulents). When succulents were excluded, the association between SLA and LWC was significant and positive. A similar trend was found for a mixed set of nonsucculent species from other floras of the world. • In the Argentine data set, SLA and LT, but not LWC, were significantly correlated with species' scores along a multivariate axis of plant resource-use strategy. • Because of its clearer ecological interpretation and its applicability across different floras, SLA appears to be the best candidate for inclusion in large comparative databases.